Videoanaliz konfliktnogo vzaimodejstvija tchekvondistov VTF v sorevnovatel'nych poedinkach - Epov, O. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Throughout the development of martial arts, the problem of assessing both the technical and tactical characteristics of an athlete and the determination (typing) of styles of action in competitive fights remains relevant. The article proposes an algorithm or identifying the types of interaction of highly qualified athletes - WTF Taekvondo players based on video analysis. The author offers a systematic analysis of the rivalry`s struggle as a changing system, which allows one to find the relationships between the elements of the system under consideration. So, in the analyzed fights it was revealed that lateral maneuvering was most often used for defense (55%), when conducting advanced and counter attacks (15%); during counterattacks (25%) and in response attacks (5%). Lateral maneuvering with the use of enemy dispersal is effective against the "step" and "shuttle". A scheme is presented that reveals the tactical meanings of lateral maneuvering. Testing the developed conflict analysis analysis algorithm with the participation of representatives of the student national team of the country gave a positive result.